The experiences of survivors of intimate partner violence in Thai women - Suwannee Sroisong; Somporn Kantharadussadee Triamchaisri; Ronnachai Kongsakon; Trude Bennett; Ratchneewan Ross (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The study on experiences of women with intimate partner violence (IPV) reveals the meanings of recovering psychological health and independence from their abuser. However, not much study has been done to reveal experiences of abused women in their attempt to recover from their past traumatic experiences in the context of Thai society. The purpose of this paper is to explore experiences of survivors of IPV in Thai women. Design/methodology/approach - Key informants included ten women who had experienced IPV and left abusive relationships. They were recruited from a provincial hospital in upper southern part of Thailand. Data were collected from in-depth interviews and analyzed using a phenomenological method. Findings - Findings showed that five themes had emerged as follows: seeking help and support; decision to terminate the abusive trap; enhancing empowerment to solve their problems; learning to forgive the abuser; and adopting the ability to stand on one's own two feet. Originality/value - The study helps shed light on the recovering of the abused women. The survivors had faced psychological suffering and economic problems. Therefore, they need supports in order to make the exit possible and to use group support to increase their strength in fighting against an abusive relationship.